Significance of a place: The Malay cultural heritage of Kerian district, Perak, Malaysia / Kamarul Bahrain Shuib and Habsah Hashim - Shuib, Kamarul Bahrain; Hashim, Habsah (Research Management Institute (RMI), 2013)
Rapid development that had taken place in most places in Malaysia as a result of favorable economic growth and political stability following the country's independence had encroached into the countryside. The rural countryside environments such as stretches of paddy fields, rustic villages, pristine forest reserves and peaceful coastal areas are slowly being eroded in the name of progress and development. The process of land use change from agriculture to development (housing, commerce and industry) had often ignored the significance and unique character of a place. Malay culture and heritage areas are areas that have Malay characteristics and are influenced by the Malay tradition and values for a long time. The countryside of the Malay heartland represents the transformation of the people, their culture and livelihood over time. However, pressure on land and eagerness for modern development threatens these areas and could destroy the 'sense of place' that has evolved. The study would focus on the existing landscape character that has evolved from the various historical periods that shaped the community, settlements and livelihood of the people living in the district. The landscape character types that will be analyzed include hills and uplands, plains, lakes, dams and settlement patterns. The elements that would be studied include the historical background, physical character, uniqueness of a place, existing use and the importance of the place to the nearby community.